A Case Report of Late Onset Mania Caused by Hyponatremia in a Patient With Empty Sella Syndrome. Issue 6 (February 2016) - Yang, Chung-Hao; Lin, Yu-Chen; Chou, Po-Han; Chen, Hung-Chieh; Chan, Chin-Hong
Abstract : Abstract: Recurrent manic-like episodes can be induced by hyponatremia possibly due to empty sella syndrome. In the present case, the patient was proven to have syndrome of inappropriate antidiuretic hormone (SIADH) secretion with manic symptoms that resolved after the normalization of the plasma sodium level. To our knowledge, this is the first case of hyponatremia-induced manic symptoms in a patient with empty sella syndrome. More attention should be paid to late-onset mania, because it may be the sign of a more serious medical problem.